A cross sectional study on the occupational airborne exposure and the prevalence of self-reported asthma, and respiratory symptoms amongst workers in selected factories in Nairobi, Kenya - Jairus Musumba; Ziporah Nganga; Yeri Kombe (Journal of Global Health Reports)
# Background